Description of the spermathecae and testicles of Triatoma melanocephala Neiva & Pinto, 1923 (Hemiptera: Reduviidae: Triatominae) - de Oliveira, Jader; Alevi, Kaio Cesar Chaboli; Nascimento, Juliana Damieli; Mendonça, Vagner José; de Araújo, Renato Freitas; da Rosa, João Aristeu [UNESP] (Sociedad Chilena de Entomologia, 2023)
Triatoma melanocephala is an endemic species of Brazil. Phenotypic (external morphology) and molecular studies were performed to contribute to the taxonomy and phylogeny of triatomines, since few studies on the internal morphology of these were found. In order to contribute to the biological, morphological and taxonomic knowledge of the subfamily Triatominae, this work describes the internal morphology of the reproductive apparatus of adult males and females of T. melanocephala. For this work 30 specimens from Jequié, Bahia, Brazil were used. Triatoma melanocephala’s reproductive system included slim spermathecae insertions, large/medium rounded terminal bodies, and irregular ellipsoid-shaped testicles with a transparent, vitreous appearance. These results contribute to the knowledge of the reproductive biology of this species of vectorial importance and show taxonomic relevance, as well as possible application in systematic studies.